2021
DOI: 10.1186/s40959-021-00094-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignancy long after acute coronary syndrome in selected urban and rural areas and comparison with smoking risk: the ABC-7* study on Heart Disease

Abstract: Background Increased cancer risk has been reported in patients with acute coronary syndrome (ACS). Objectives To investigate geographic differences in risk malignancy long after ACS. Methods We enrolled 586 ACS patients admitted to hospitals in three provinces in the Veneto region of Italy in this prospective study. Patient’s residency was classified into three urban and three nearby rural areas. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…The higher cancer mortality in residents of the northern rural area in our study may be caused by differences in cancer incidence, as we have previously reported a higher incidence of cancer in the same area (14). Jansen et al have also attributed the higher cancer mortality in the more deprived areas in their study to a disparity in cancer incidence (36).…”
Section: Cox Regressionsupporting
confidence: 58%
See 4 more Smart Citations
“…The higher cancer mortality in residents of the northern rural area in our study may be caused by differences in cancer incidence, as we have previously reported a higher incidence of cancer in the same area (14). Jansen et al have also attributed the higher cancer mortality in the more deprived areas in their study to a disparity in cancer incidence (36).…”
Section: Cox Regressionsupporting
confidence: 58%
“…We recently reported that ACS patients have a higher longterm risk of cancer than the general population (4). Among lifelong ACS patients, we also documented a significant difference in the incidence and prevalence of malignancy across different parts of the Veneto region, with the northern rural area having the greatest risk (14). 3 | Cox regression and Fine-Gray competing risk regression analysis of non-neoplastic and neoplastic mortality risk over 22 years of follow-up after ACS with the interaction for risks between the six geographic areas after excluding patients who had malignancy and were still alive (n = 519).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations